EVALUATION OF AUTONOMIC DYSFUNCTION BY HEART RATE VARIABILITY ANALYSIS IN TYPE 2 DIABETES MELLITUS - Phurpa; Ferdousi, Sultana (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Objective: Cardiac autonomic neuropathy (CAN) is a severe and common, yet highly underdiagnosed, complication of Type 2 diabetes mellitus (T2DM). Subclinical CAN may have reduced heart rate variability (HRV) but normal Ewing battery test. This study was performed to evaluate the importance of 5 minutes HRV for the detection of autonomic dysfunction in T2DM without (CAN-T2DM). Methods: This cross-sectional observational study was conducted at the Department of Physiology, Bangabandhu Sheikh Mujib Medical University (BSMMU) on 30 recently diagnosed T2DM (RT2DM) and 54 long-term CAN-male T2DM patients (LT2DM), aged 45-55 years, from the Endocrinology Out Patient Department of BSMMU, Dhaka. 30 age and body mass index matched apparently healthy male subjects were control. Ewing battery test was used to rule out CAN positive T2DM. HRV data were recorded by a polyrite-D and analyzed by software. HRV was assessed by time domain method. For statistical analysis, ANOVA and unpaired t-test were used. Results: Mean RR, standard deviation of NN intervals (SDNN) (p<0.05), and root mean square of the successive differences (RMSSD) were significantly (p<0.001) lower, and mean HR and SDNN/RMSSD were (p<0.001) significantly higher in LT2DM compared to RT2DM and control. In addition, SDNN was also significantly (p<0.05) lower in RT2DM than that of control. Conclusions: Results conclude that autonomic dysfunction may occur in both LT2DM and RT2DM patients without neuropathy and 5 minutes HRV test is an important tool for detecting subclinical CAN. Keywords: Type 2 diabetes mellitus, Cardiac autonomic neuropathy, Heart rate variability.